Proceedings of the Fourth Conference on Applied Natural Language Processing - 1994
DOI: 10.3115/974358.974380
|View full text |Cite
|
Sign up to set email alerts
|

Three heads are better than one

Abstract: Machine translation (MT) systems do not currently achieve optimal quality translation on free text, whatever translation method they employ. Our hypothesis is that the quality of MT will improve if an MT environment uses output from a variety of MT systems working on the same text. In the latest version of the Pangloss MT project, we collect the results of three translation engines --typically, subsentential chunks --in a chart data structure. Since the individual MT systems operate completely independently, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 5 publications
0
28
0
1
Order By: Relevance
“…In the competitive combination mode (b), the three translation engines separately translate the input sentence or the components of the input sentence, and the system then selects the best of the three results as the output (Frederking, and Nirenburg 1994;Nomoto 2003Nomoto , 2004. Several studies have shown that the overall performance of the competitive arrangement can in fact, as hoped, be better than that of the best participating MT engine (Hogan and Frederking 1998;Cavar, et al 2000;Akiba et al 2002).…”
Section: Mt and The Usermentioning
confidence: 99%
“…In the competitive combination mode (b), the three translation engines separately translate the input sentence or the components of the input sentence, and the system then selects the best of the three results as the output (Frederking, and Nirenburg 1994;Nomoto 2003Nomoto , 2004. Several studies have shown that the overall performance of the competitive arrangement can in fact, as hoped, be better than that of the best participating MT engine (Hogan and Frederking 1998;Cavar, et al 2000;Akiba et al 2002).…”
Section: Mt and The Usermentioning
confidence: 99%
“…System combination has enjoyed great success in many domains, such as automatic speech recognition (Fiscus, 1997;Mangu et al, 2000), machine translation (Frederking and Nirenburg, 1994;Bangalore et al, 2001) and parsing (Henderson and Brill, 1999;Sagae and Lavie, 2006). However, only a handful of papers have leveraged this idea for summarization.…”
Section: Related Workmentioning
confidence: 99%
“…In one of the first publications on system combination in MT, Frederking and Nirenburg [13] create a chart structure where target language phrases from each system are placed according to their corresponding source phrases, together with their confidence scores. A chart-walk algorithm is used to select the best translation from the chart.…”
Section: Related Workmentioning
confidence: 99%